Identification of a peptide motif that potently inhibits two functionally distinct subunits of Shiga toxin - Miho Watanabe-Takahashi (Nature Portfolio, 2021)
Watanabe-Takahashi, Tamada, Senda et al. identify a tetravalent peptide that inhibits Shiga toxin (Stx), a major virulence factor of enterohemorrhagic Escherichia coli, by targeting its receptor-binding. On the other hand, a monomeric peptide containing the same motif occupies the Stx catalytic cavity, suggesting that this peptide motif can inhibit two subunits of Stx.